Genomics of speciation and introgression in Princess cichlid fishes from Lake Tanganyika - Hugo F. Gante; Michael Matschiner; Martin Malmstrøm; Kjetill S. Jakobsen; Sissel Jentoft; Walter Salzburger (Molecular Ecology, 2016)
How variation in the genome translates into biological diversity and new species originate has endured as the mystery of mysteries in evolutionary biology. African cichlid fishes are prime model systems to address speciation‐related questions for their remarkable taxonomic and phenotypic diversity, and the possible role of gene flow in this process. Here, we capitalize on genome sequencing and phylogenomic analyses to address the relative impacts of incomplete lineage sorting, introgression and hybrid speciation in the Neolamprologus savoryi ‐complex (the ‘Princess cichlids’) from Lake Tanganyika. We present a time‐calibrated species tree based on whole‐genome sequences and provide strong evidence for incomplete lineage sorting in the early phases of diversification and multiple introgression events affecting different stages. Importantly, we find that the Neolamprologus chromosomes show centre‐to‐periphery biases in nucleotide diversity, sequence divergence, GC content, incomplete lineage sorting and rates of introgression, which are likely modulated by recombination density and linked selection. The detection of heterogeneous genomic landscapes has strong implications on the genomic mechanisms involved in speciation. Collinear chromosomal regions can be protected from gene flow and harbour incompatibility genes if they reside in lowly recombining regions, and coupling can evolve between nonphysically linked genomic regions (chromosome centres in particular). Simultaneously, higher recombination towards chromosome peripheries makes these more dynamic, evolvable regions where adaptation polymorphisms have a fertile ground. Hence, differences in genome architecture could explain the levels of taxonomic and phenotypic diversity seen in taxa with collinear genomes and might have contributed to the spectacular cichlid diversity observed today.